Comparative Analysis of IT Management Tools in Healthcare - Annam, Sri Nikhil (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
Healthcare systems today rely heavily on IT management tools for automation of patient care, increased operational efficiency, and simplification of the decision-making processes. This paper focuses closely on some of the major IT tools such as Electronic Health Records, Health Information Exchanges, CRM systems, ERP systems, and IT security frameworks. This research identifies some of the key trends, challenges, and opportunities surrounding healthcare IT through a feature and scalability analysis, checking for standard compliance, and assessing the general effects associated with such tools. The conclusion for the study brings actionable recommendations about ways to enhance IT tool adoption and optimize integration.